2011
DOI: 10.1111/j.1365-2885.2011.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of 14‐day oral vedaprofen and tolfenamic acid treatment on renal function, hematological and biochemical profiles in healthy cats

Abstract: The objective of this study was to evaluate the effects of the nonsteroidal anti-inflammatory drugs vedaprofen and tolfenamic acid on renal function after oral administration for 2 weeks in healthy cats. Experiments were performed using nineteen domestic short-haired cats randomly divided into one control (n=6) and two treatment groups. All cats in the first (n=6) and second treatment groups (n=7) received vedaprofen (0.5 mg/kg/day) and tolfenamic acid (4 mg/kg/day), respectively. During the experiment, renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The effects of tolfenamic acid and robenacoxib in cats with bleeding disorders are beyond the scope of the present study. Similar to our study, previous research has found that tolfenamic acid [ 12 ] and robenacoxib [ 13 ] have no effect on renal function, hematological profiles, or biochemical profiles in healthy cats. Nonetheless, care should be taken to administer NSAIDs to cats with thrombocytopenia or anemia, or to those receiving anticoagulants, as NSAIDs may prolong coagulation time.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The effects of tolfenamic acid and robenacoxib in cats with bleeding disorders are beyond the scope of the present study. Similar to our study, previous research has found that tolfenamic acid [ 12 ] and robenacoxib [ 13 ] have no effect on renal function, hematological profiles, or biochemical profiles in healthy cats. Nonetheless, care should be taken to administer NSAIDs to cats with thrombocytopenia or anemia, or to those receiving anticoagulants, as NSAIDs may prolong coagulation time.…”
Section: Discussionsupporting
confidence: 91%
“…Tolfenamic acid is among the conventional non-selective COX inhibitors commonly used in Thailand [ 12 ]. Non-selective NSAIDs inhibit both COX-1 and COX-2, leading to reduce inflammation due to the inhibition of prostaglandin production [ 20 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NSAIDs act mainly through the inhibition of COX activity in the biochemical cascade that leads to prostaglandin synthesis, and there are selective NSAIDs for COX-2 inhibition (KHWANJAI et al, 2011). COX-1 and COX-2 are involved in renal blood flow and tubular function regulation; therefore, selective COX-2 NSAIDs do not necessarily cause less renal side effects.…”
Section: Palavras-chavementioning
confidence: 99%